HUBUNGAN TINGKAT PEGETAHUAN DAN SIKAP DENGAN KESIAPAN MENGHADAPI MENARCHE PADA REMAJA PUTRI DI SD PLUS DARUL ULUM JOMBANG - Prastiwi, Nur Wasilatul Arhamiah Dewi; Sasmito, Nanang Bagus; Zatihulwani, Eliza Zihni (LPPM STIKES HUSADA JOMBANG, 2024)
Menarche is the first menstruation that will naturally be experienced by all women and as a sign of the entry of puberty. Recently the age pf menarche is getting earlier. Thus, causing unpreparedness in terms of knowledge, attitude and readiness. So, this study aims to determine the relationship between the level of knowledge and attitudes with readiness to face menarche in adolescent girls at SD Plus Darul Ulum Jombang. This study used correlational analytical method with cross sectional approach. The samples in this study were taken with a total sampling technique of 40 respondents consisting of classes IV, V and VI who had no experienced menarche. Data collection instruments in the form of questionnaires and interviews. Using univariate and bivariate data analysis using the Spearman Rank (Rho) test. The result of the univariate analysis found that the level of knowledge was sufficient for 26 respondents (65%), had a fairly good attitude of 29 respondents (72.5%) and all respondents were ready to face menarche of 40 respondents (100%). The results of the bivariate analysis showed no relationship between knowledge and readiness to face menarche (p = 0.288 > 0.05), on the contrary there was a significant relationship between attitude and readiness to face menarche (p = 0.00 < 0.005). it can be concluded that the better the level of knowledge that young women have, the better the attitude of young women who are ready to face menarche. So that this research can provide input to the school so that it can work with health workers in providing menstrual health management education in preparing menarche for adolescent girls using learning media that is easy to understand.